Negative Corneal Fluorescein Staining as an Exceptionally Early Sign of Acanthamoeba Keratitis: A Case Report. Issue 11 (November 2021) - Korkmaz, Ilayda; Barut Selver, Ozlem; Simsek, Cem; Palamar, Melis
Abstract : Objectives: To report the negative fluorescein staining as an early sign of Acanthamoeba keratitis (AK). Methods: Case report and brief review of related literature. Report of Case: A 30-year-old, contact lens wearer, woman presented with mild irritation and pain in the right eye. The best-corrected visual acuity (BCVA) was 20/20 in both eyes. Slit-lamp examination revealed a peripheral corneal infiltration. Empirical antimicrobial therapy was initiated. Within the third day, peripheral corneal opacity regressed but a Y-shaped linear epitheliopathy with a negative fluorescein staining, because of a ridge-like epithelial irregularity, was observed in the central cornea. Clinical findings progressed rapidly. Confocal microscopy revealed hyper-reflective cysts with the typical double-ring sign consistent with AK. Therefore, topical chlorhexidine and propamidine were initiated. Clinical findings regressed subsequently. The final BCVA was 20/20 in both eyes. Conclusion: Acanthamoeba keratitis usually manifest as superficial epitheliopathy and progresses to the stroma. Findings may be obscure or atypical; comprehensive and careful examination may reveal mild findings in the early stages.